An Analysis Of First-Grade Students' Beginning Writing Skills In Elementary Education - Selda Carnelia; Kasmawati Kasmawati; La Sisi (CV. Gerasi Insan Nusantara, 2025)
This study aimed to describe the beginning writing skills of first-grade students, identify the difficulties they experienced, and examine the strategies used by teachers to address these difficulties at an elementary school in South Konawe Regency. A descriptive qualitative approach was employed, with the study conducted from March to April 2026. The participants consisted of a first-grade teacher and students. Data were collected through observation, interviews, beginning writing assessments, and documentation, and were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings showed that students' beginning writing skills were generally satisfactory, although more than five students continued to require intensive assistance. The main difficulties involved forming vowel and consonant letters correctly, writing simple sentences, applying capitalization and punctuation, maintaining handwriting neatness, and spacing words appropriately. Some students also required additional time to complete writing tasks. These difficulties were associated with limited writing practice, insufficient habits of reviewing completed work, and inadequate mastery of basic writing conventions. To address these challenges, the teacher implemented routine writing practice, individualized guidance, demonstrations of correct writing, engaging instructional media, and continuous encouragement. The study concludes that although the overall level of beginning writing skills was satisfactory, targeted and sustained support remains necessary to strengthen students' foundational writing abilities.